Achieving China's Intended Nationally Determined Contribution and its co-benefits: Effects of the residential sector. (20th January 2018) - Xing, Rui; Hanaoka, Tatsuya; Kanamori, Yuko; Masui, Toshihiko
Abstract: In preparation for the 21st Conference of Parties (COP21) held in December 2015, the participating parties under the UN Framework Convention on Climate Change (UNFCCC) agreed to submit their own targets for national greenhouse gas emission reductions and mitigation, and adaptation actions that they intended to take under the post-2020 international framework for climate change. They were called Intended Nationally Determined Contributions (INDCs). One of the important actions by 2030 in China's INDC is to lower carbon dioxide (CO2 ) emissions per unit of GDP by 60%–65% from 2005 levels. The purpose of this study is 1) to examine the efforts on China's residential sector in achieving the CO2 reduction target stated in China's INDC, 2) to estimate the range of carbon prices and mitigation potential in the INDC targets, and 3) to analyze the co-benefits of low carbon measures to reduce emissions of major short-lived climate pollutants and air pollutants in the residential sector, such as black carbon (BC), fine particulate matter (PM2.5 ), and sulfur dioxide (SO2 ). To account for climate diversity and its impact on household energy service demands, our analysis divides China into 31 sub-national regions. It was found that the residential sector has significant reduction potential to succeed with "no-regret" CO2 reduction measures. To achieve the range of China's INDC targets, households in both rural and urban China must implement more efficient technologies and marginal abatement in the range of around $40–$60 US/tCO2 . Compared to the FIX scenario, CO2, BC, PM2.5, and SO2 emissions from the residential sector in the whole China are respectively reduced by 38%, 21%, 16%, and 31% in 2030 in the lower boundary of the INDC targets. However, reduction rates vary across provinces due to climatic variations and economic disparities. For example, cold provinces contribute more to the total emission reductions than warm provinces, under a national carbon emission cap to achieve the INDC targets. It is also important to note that there are large co-benefits to reducing air pollutants due to low carbon measures, thus achieving the INDC targets will help improve indoor air quality in the residential sector, especially in rural areas.